Study of Beni Haroun dam pollution (Algeria). Issue 6 (1st February 2016) - Nadir, Marouf; Boualem, Remini
Abstract: The aim of this work is to study pollution parameters evolution in Kebir-Rhumel basin over 10 years, considering data from four hydrometric stations, and analyze physicochemical and bacteriological characteristics of Beni-Haroun dam streamwater over 5 years. Some analyzed parameters are in relation with water natural structure such as (pH), conductivity, turbidity, chloride ions, sulfate ions…etc. and undesirable substances as nitrates ( ) and phosphates ( ) excessive concentrations, which are the main factors responsible for algae proliferation and eutrophication phenomenon acceleration. Thus, pollution indicator parameters as chemical oxygen demand (COD), biochemical oxygen demand (BOD5 ), dissolved, and saturated oxygen were also studied. The elaborated work had shown increasing turbidity and suspended matter (SM) in Beni-Haroun dam and Kebir-Rhumel basin, where sulfate concentrations ( ) are noticeable in different samples. BOD5, COD, dissolved, and saturated oxygen values indicate organic, chemical, and microbiological water contamination in both dam streamwater and basin catchment.